Corrections to the Linvill Normalization Procedure in the NEC Basic Scattering Code - Albus, Richard D. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Corrections to the Linvill Normalization Procedure in the NEC Basic Scattering Code